Utilization of Audio-Visual Media to Develop Students' Critical Thinking Skills in Science Subject for Fifth Grade - Utami, Ratnasari Diah; Cholifah, Muthia Rachmawati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The study aims to be achieved are (1) Measuring the effect of using audio-visual media on the development of critical thinking skills of elementary school students in science learning and (2) Evaluating the effectiveness of audio-visual media in facilitating in-depth understanding of human circulatory system material. Methodology: The study used quantitative methods with a Quasi-Experimental Design design. Results: The results of average value of students' initial critical thinking skills (pretest value) in the experimental class was 60.60 and the control class was 55.40. Then the average value of students' final critical thinking skills (posttest value) in the experimental class was 85.53 and the control class was 77.06. Based on the hypothesis proposed, it shows that there is a significant increase in the critical thinking skills of students who use audiovisual media, with the average posttest value higher than the control group. From the averages that have been explained, it can be concluded that there is an influence in the use of audio-visual media on the development of critical thinking skills of elementary school students in science learning. Applications/Originality/Value: This research presents a novel approach by examining the use of audio-visual media to develop critical thinking skills in fifth-grade science students. Unlike previous studies that generally focus on improving learning outcomes, this study specifically explores its impact on critical thinking, particularly for complex topics like the human circulatory system, within a primary school setting.